Single-junction organic solar cells with over 19% efficiency enabled by a refined double-fibril network morphology - Zhu, Lei; Zhang, Ming; Xu, Jinqiu; Li, Chao; Yan, Jun; Zhou, Guanqing; Zhong, Wenkai; Hao, Tianyu; Song, Jiali; Xue, Xiaonan; Zhou, Zichun; Zeng, Rui; et al. (Nature materials, 2022)
In organic photovoltaics, morphological control of donor and acceptor domains on the nanoscale is the key for enabling efficient exciton diffusion and dissociation, carrier transport and suppression of recombination losses. To realize this, here, we demonstrated a double-fibril network based on a ternary donor–acceptor morphology with multi-length scales constructed by combining ancillary conjugated polymer crystallizers and a non-fullerene acceptor filament assembly. Using this approach, we achieved an average power conversion efficiency of 19.3% (certified 19.2%). The success lies in the good match between the photoelectric parameters and the morphological characteristic lengths, which utilizes the excitons and free charges efficiently. This strategy leads to an enhanced exciton diffusion length and a reduced recombination rate, hence minimizing photon-to-electron losses in the ternary devices as compared to their binary counterparts. The double-fibril network morphology strategy minimizes losses and maximizes the power output, offering the possibility of 20% power conversion efficiencies in single-junction organic photovoltaics. The morphology of donor–acceptor blends in organic photovoltaics dictates the efficiency of the exciton dissociation and charge diffusion, and thus the final device performance. Here, the authors show that filament assembly helps to maximize the output, further enabling a power conversion efficiency greater than 19%.